Tröger’s Base Derivative-catalyzed Ugi-Smiles Reaction Involving Aliphatic Aldehydes - Dong, Meng-xue; Cui, Hao; Wan, Yu; Yuan, Rui; Wu, Hui (Letters in Organic Chemistry, 2025)
Ugi-Smiles reactions play an important role in the field of organic synthesis and pharmaceutical chemistry. However, due to their low reactivity, less electrophilic aliphatic aldehydes have never been used as substrates. To expand the range of substrates for the reaction, a bis(<span class=
Keywords: thioimidazolidinones